1992
DOI: 10.1073/pnas.89.24.11740
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenin and recombinant bone morphogenetic protein 2B are chemotactic for human monocytes and stimulate transforming growth factor beta 1 mRNA expression.

Abstract: Subcutaneous implantation of deminerli bone matrix initiates a sequence of developmental events, which nate in endochondial bone formation. During early stages of development of matrix-induced Impts, ED1, Tapositive monocytes-macrophages were observed, sgeting that in the initial phases of the endochondral bone formation de, the bone-inductive protein osteogenin and related bone morphogenetic proteins (BMPs) might serve as potent chemoattractants to recruit circulating monocytes. In this investigation, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
1
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(119 citation statements)
references
References 51 publications
4
110
1
4
Order By: Relevance
“…Cunningham et al 44 showed that BMPs have profound effects on the recruitment of monocytes, known precursors of tissue macrophages. Subsequent studies have shown that BMP receptors are robustly expressed on monocytes and tissue macrophages 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Cunningham et al 44 showed that BMPs have profound effects on the recruitment of monocytes, known precursors of tissue macrophages. Subsequent studies have shown that BMP receptors are robustly expressed on monocytes and tissue macrophages 45 .…”
Section: Discussionmentioning
confidence: 99%
“…During development, BMP-2/4 enhance cell proliferation, stimulate cell survival pathways, and induces self-renewal of stem cells (Ying et al, 2003). BMP-2/4 regulate postnatal tissues, which include the differentiation of ovarian granulosa cells (Souza et al, 2002) and the migration of smooth muscle and endothelial cells (Cunningham et al, 1992;Willette et al, 1999;Langenfeld and Langenfeld, 2004). BMPs mediate signaling by activating serine kinase receptors, which activate the Smad-1/5 transcription factor (Yamashita et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is reminiscent of the increased TGF-␤1 expression in a human osteoblast cell line by BMP-2 22 and in human monocytes by BMP-4. 23 Because we did not find increased TGF-␤1 mRNA levels in a series of stromal cells stimulated with BMP-9, our data suggest that BMP-9 does not act on bone marrow stroma. However, a more definitive conclusion requires the determination of TGF-␤1 mRNA levels in primary stromal cells exposed to BMP-9.…”
Section: Discussionmentioning
confidence: 69%